Topographic control of order-disorder phase transitions in a quasi-2D granular system - Downs, James Gordon (2023)
The focus of current research in two-dimensional phase transitions has shifted towards non-equilibrium systems such as active matter and fluid dynamics. However, unlike in equilibrium systems, we lack a complete framework to describe their behaviour. Although previous work has shown that some basic concepts from statistical mechanics can be applied to non-equilibrium systems, the extent to which they can be applied remains unclear. One intriguing problem in equilibrium systems is the two-dimensional hard-disc liquid-to-crystal phase transition. The nature of this phase transition differs from that in three-dimensions and was, until recently, a matter of much debate. Extending this debate, two-dimensional granular systems have also been studied to investigate the applicability of hard-disc model descriptions to non-equilibrium systems. Granular systems are convenient for manipulation and offer easy observations at the particle level and therefore represent an ideal test case for these investigations. In this thesis, I present an investigation of the order-disorder phase transition in a 2D driven granular system. Previous research has shown that these systems undergo a continuous two-step phase transition. We explore a mechanism for changing the nature of this transition from continuous to first-order by introducing a triangular lattice of dimples milled into the surface. The change in phase transition behaviour, for the system we focus on for much of this thesis, enables further study of other behaviours from equilibrium physics, such as hysteresis, surface tension and wetting.